PERAN DAN KEWENANGAN OTORITAS JASA KEUANGAN (OJK) TERHADAP KEAMANAN TRANSAKSI DI PASAR MODAL - Elvira Fitriyani Pakpahan; Eric Kurniawan; Kelfin Candra; Silvi Yanti (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
The word "security" is the most popular word that is often asked back when someone is introduced for stock investment for the first time.The large number of crimes that have occurred in capital market activities since 2009 until now has certainly led to much speculation about the authority of the OJK body responsible for overseeing capital markets so this is a problem in this study. The problem is the role and authority of the government in mitigating Indonesian capital market crime and transaction security in the capital market. Keywords :security, OJK's role and authority.